Polymeric Electrospun Fibrous Dressings for Topical Co-delivery of Acyclovir and Omega-3 Fatty Acids - Costa, Tiago; Ribeiro, Artur; Machado, Raul; Ribeiro, Clarisse; Lanceros-Mendez, Senentxu; Cavaco-Paulo, Artur; Almeida, Andreia; das Neves, José; Lúcio, Marlene; Viseu, Teresa (Frontiers in Bioengineering and Biotechnology, 2019)
Herpetic infections caused by Herpes simplex virus (HSV) are among the most common human infections, affecting more than two quarters of the world's population. The standard treatment for orofacial herpes is the administration of antiviral drugs, mainly acyclovir (ACV). However, current products are mostly based on semisolid formulations that have limited ability to promote drug skin penetration and tend to leak from the application site, thus showing reduced ability to sustain local drug residence. This work reports on the production of poly (ε-caprolactone) (PCL) fibrous matrices with ACV and omega-3 fatty acids (ω3) for application as dressings to the topical treatment of orofacial herpes. PCL fibrous matrices with the co-incorporated bioactive compounds were obtained by electrospinning and characterized regarding their morphology, chemical, physical and mechanical properties. The potential use of the developed polymeric fibrous matrices for topical applications was evaluated by: (i) the release kinetics of the bioactive compounds; (ii) the occlusive factor of the fibrous mat; (iii) ACV skin permeation capacity and (iv) the cytotoxicity in a keratinocyte cell line. PCL fibrous matrices loaded with the bioactive compounds presented a smooth morphology and a good balance between flexibility and hardness essential to be durable for handling, while having a desirable texture to be used comfortably. The fibrous mat also provided a sustained release of ACV during 96 h and improved the skin permeability of this drug (Kp=0.00928 ± 0.000867 cm/h) presenting also high porosity (74 %) and a water vapor transmission rate (WVTR) of 881 ± 91 g/m2day, essential to maintain moist and oxygen for faster healing of herpes lesions. Furthermore, cytotoxicity studies suggest that the fibrous mat are safe for topical application. Overall, the PCL based electrospun fibrous matrices with ACV and ω3 hereby described have the potential to be used as therapeutic bandage systems for the treatment of orofacial herpes.